The Relationship Between Work Attitudes and Work Environment on Employee Performance at the Talang Jambe Health Center, Palembang - Lendriyani; Zulaikha Agustinawati; Riana Dewi; Sri Aisyah Hidayati; Henni Febriawati (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2025)
Employee performance (work achievement) as a result of work in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This study aims to determine the relationship between work attitudes and work environment on employee performance at the Talang Jambe Health Center, Palembang in 2024. The research was conducted on August 12, 2024, where the research was conducted at the Talang Jambe Health Center, Palembang City. The population in this study were all employees working at the Talang Jambe Health Center, a total of 32 employees. The sample in this study was taken from the total population, namely 32 people with a sampling technique using Total Sampling or the entire population. Based on statistical tests, there is a relationship between attitude (p value = 0.002 <0.05), work environment (p value = 0.013 <0.05) on employee performance at the Talang Jambe Health Center, Palembang City in 2024. It is hoped that more attention will be paid to good work attitudes and work environments, so that employees work optimally.Kinerja karyawan (prestasi kerja) sebagai hasil kerja secara kualitas dan kuantitas yang dicapai seorang karyawan dalam melaksanakan tugasnya sesuai dengan tanggung jawab yang diberikan kepadanya. Penelitian ini bertujuan untuk mengetahui hubungan sikap kerja dan lingkungan kerja terhadap kinerja karyawan di Puskesmas Talang Jambe Palembang tahun 2024. Pelaksanaan penelitian dilakukan pada 12 Agustus 2024, tempat penelitian dilaksanakan di Puskesmas Talang Jambe Kota Palembang. Populasi pada penelitian ini adalah seluruh karyawan yang bekerja di puskesmas Talang Jambe sebanyak 32 orang karyawan. Sampel dalam penelitian ini diambil keseluruhan dari total populasi yaitu 32 orang dengan teknik pengambilan sampel secara Total Sampling atau seluruh jumlah populasi. Berdasarkan uji statistic ada hubungan antara sikap (p value =0,002 <0,05), lingkungan kerja (p value =0,013 <0,05) terhadap kinerja karyawan diPuskesmas Talang Jambe Kota Palembang tahun 2024. Diharapkan lebih memperhatikan tentang sikap kerja dan lingkungan kerja yang baik, agar karyawan bekerja secara maksimal.